La limite entre orphisme et pythagorisme en Italie préromaine et le problème du terme orphico-pythagoricien - Corentin Voisin (Frontière·s)
Since the end of the 18th century, researchers have often confused Orphism and Pythagoreanism, leading to the creation of the syntagma Orphico-Pythagorean. However, this remains problematic both in the field of historical and archaeological studies, as it hides paradigm errors in the understanding of ancient Greek religion on one hand and a vague interpretation of Pythagoreanism on the other hand. The present study will give brief definitions of Orphism and Pythagoreanism in the light of recent works on these topics and then trace the history of the term Orphico-Pythagorean. This historiographical approach highlights the improper usage of the term, particularly in archaeology, for periods prior to the last two centuries of the Roman Empire. The analysis of certain archaeological contexts will then lead to a stricter identification of Orphism and Pythagoreanism.